Influence of Ways to Thaw Bull Sperm on Its Quality - Shakhova , Yulia; Paliy, Anatoliy; Paliy, Andrii; Shkromada , Oksana; Musiienko , Yurii; Bondarenko, Irina (Problems of Cryobiology and Cryomedicine, 2021)
Probl Cryobiol Cryomed 2021; 31(3): 277–282